Employment during the Pandemic Based on Regulation of the Minister of Manpower No. 21 of 2021 - Pratiti Alma Nurlita; Mahendra Akbar Rachmadani; Putri Monica; Rachma Nadya Pratama Putri; Saputri Setyo Nur Haryani; Aseka Malikus Zachwa (Proceeding International Conference Restructuring and Transforming Law, 2022)
This study aims to determine the legal protection for workers affected by the Covid-19 outbreak. Article 88 letter a paragraph 1 UURI No. 11 of 2020 concerning Job Creation, states that "The rights of workers/laborers to wages arise when there is a working relationship between the worker/labourer and the entrepreneur and ends when the employment relationship is terminated." Therefore, based on the considerations of UURI Number 11 of 2020 letter e, considering that efforts to change regulations relating to the convenience, protection, and empowerment of cooperatives and micro, small and medium enterprises, improvement of the investment ecosystem, and acceleration of national strategic projects, including increased protection and workers' welfare is carried out through changes to sector laws that do not yet support the realization of synchronization in ensuring the acceleration of work creation, so that legal breakthroughs are needed that can solve various problems in several laws into one law comprehensively. It can be concluded that the existence of the Law on the protection of workers' wages and protection for workers in their place of work, the company can postpone the payment of wages received by workers (if the company cannot pay it according to the minimum wage limits). An agreement was made with workers to suspend. And with the spread of Covid-19, the government issued a ministerial regulation regarding employment No.21 of 2021, so that it can provide legal protection for workers/laborers. so that legal breakthroughs are needed that can solve various problems in several laws into one law comprehensively. It can be concluded that the existence of the Law on the protection of workers' wages and protection for workers in their place of work, the company can postpone the payment of wages received by workers (if the company cannot pay it according to the minimum wage limits). An agreement was made with workers to suspend. And with the spread of Covid-19, the government issued a ministerial regulation regarding employment No.21 of 2021, so that it can provide legal protection for workers/laborers. so that legal breakthroughs are needed that can solve various problems in several laws into one law comprehensively. It can be concluded that the existence of the Law on the protection of workers' wages and protection for workers in their place of work, the company can postpone the payment of wages received by workers (if the company cannot pay it according to the minimum wage limits). An agreement was made with workers to suspend. And with the spread of Covid-19, the government issued a ministerial regulation regarding employment No.21of 2021, so that it can provide legal protection for workers/laborers. the company can postpone the payment of wages received by workers (if the company cannot pay it according to the minimum wage limit). An agreement was made with workers to suspend. And with the spread of Covid-19, the government issued a ministerial regulation regarding employment No.21 of 2021, so that it can provide legal protection for workers/laborers. the company can postpone the payment of wages received by workers (if the company cannot pay it according to the minimum wage limit). An agreement was made with workers to suspend. And with the spread of Covid-19, the government issued a ministerial regulation regarding employment No.21 of 2021, so that it can provide legal protection for workers/laborers.